Symptomatische karpale Koalition zwischen Os scaphoideum, Os trapezium und Os trapezoideum mit ipsilateraler Daumenhypoplasie = Symptomatic carpal coalition of scaphoid, trapezium and trapezoid with coexisting ipsilateral hypoplasia of the thumb - Ahrens, Carsten; Unglaub, Frank (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2015)
We present the case of a 54-year-old woman with symptomatic coalition of scaphoid, trapezium and trapezoid as well as a coexisting ipsilateral hypoplasia of the thumb.
Gesehen am 20.11.2018